Providing nano packaging standards for pharmaceutical products in accordance with international laws - Wesam R. Kadhum; Aktris Nuryanti; Chugaeva, K.M.; Layth Hussein (International Journal of Medical Toxicology and Legal Medicine, 2024)
Today, nanotechnology is known as one of the newest methods in improving the quality, health and packaging of referee materials. Polymer nanocapsules have a special ability to store and release the carrier substance. Packaging is one of the important issues in the field of storage of medicinal materials, and the use of nanoscience can improve the quality and efficiency of packaging materials. Many of the materials that are currently used for packaging pharmaceuticals are non-degradable, which increase environmental pollution. Recently, polymer nanocomposites have been considered for the packaging of pharmaceuticals, which protect the products from physical damage and pollution. Also, smart packaging systems are made with the help of nano-sensors that are sensitive to the release of chemicals caused by the spoilage of medicines and by changing the color, it warns of the spoilage of the medicinal substance. In this article, different types of nanoparticles along with their different applications, the use of nanocomposites, nanosensors and are investigated. Also, in recent years, the rapid growth of nanotechnology has raised challenges in the field of health and safety of nanomaterials. Standardization is one of the first steps to assess and control risks resulting from nanotechnology. This study was conducted with the aim of reviewing the national standards of Iran in relation to the safety, health and environmental aspects of nanotechnology